(3fWGb GdbhI GdedReI dEJaGb GdJMcje (B/ s - (3CSGeI eUWai CMeO CMeO YOSs; (3SejMI e`UWai GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3MQUJ gPg GdOQGSI Ydi GHQGR GdJfXje GdbGfhfj dfWGb GdGJaGb GdJMcjei ShGA ef GdfGMjI GdehVhYjI(B: (3Gh ef GdfGMjI GdTNUjI Ydi VhA GdbhGYO GdeYJHQI ef GdGUhd GdYGeI ai GdGdJRGeGJ h GdQhGHW GdbGfhfjI HZV GdfXQ Yf Ci JTQjY hWfi eMOO(B: (3h cPG GdVeGfGJ GdGLQGFjI GdGSGSjI ai GdJbGVj HUaI YGeI(B. (3h JJHfi eY LGfH ef Gdabg bUQ GdJaSjQ GdVjb dGJaGb GdJMcje Ydi GdJMcje GdhWfi(B. (3CeG HGdfSHI ddJMcje GdJLGQi GdOhdi(B: (3ajJYjf GJHGY JaSjQ hGSY dGJaGb GdJMcje(B: (3aEPG eG GJab WQai GdYdGbI PGJ GdWGHY GdJLGQi GdOhdi Ydi GddLhA ddJMcje(B: (3ajJYjf JaSjQ GdGJaGb JaSjQG hGSYkG HMjK jchf GdJaSjQ dUGdM eO fWGb GdJMcje h djS JbjjOg(B. (3ceG JJHfi ePgH GWdGb eHOC GdJONd h GdGONGd ai NUheI GdJMcje Ydi ZQGQ NUheI GdOYhi GeGe bVGA GdOhdIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2018s
(3HHdjhLQGajG(B: (3UaMGJ (B364-371s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GJaGb GdJMcjes; (3gjFI GdJMcjes; (3GdGJaGb GdJMcjejs; (3GdYQa hGdYOGdI jcedGf GdGJaGb GdJMcjejs; (3eTGQWI GdJMcjes; (3eHOG GSJbdGd GJaGb GdJMcjes; (3GdYbO GdeeJOs; (3GdJMcje ZjQ GdeHGTQs; (3GdOYhi GdJMcjejI GdeHGTQIs; (3NWGH GdVeGfs; (3GdJONd hGdGONGd aj NUheI GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs